2017
DOI: 10.1107/s2052252517013264
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth-based quaternary Heusler compoundsMCoVZ(M= Lu, Y;Z= Si, Ge) with tunable band characteristics for potential spintronic applications

Abstract: Magnetic Heusler compounds (MHCs) have recently attracted great attention since these types of material provide novel functionalities in spintronic and magneto-electronic devices. Among the MHCs, some compounds have been predicted to be spin-filter semiconductors [also called magnetic semiconductors (MSs)], spin-gapless semiconductors (SGSs) or half-metals (HMs). In this work, by means of first-principles calculations, it is demonstrated that rare earth-based equiatomic quaternary Heusler (EQH) compounds with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(34 citation statements)
references
References 83 publications
0
33
0
1
Order By: Relevance
“…The general spin polarization ratio can be estimated as ¼ " À # = " þ # , in which " and # represent the spin-up states and spin-down states, respectively, extracted from the TDOS spectrum. AgCuF 3 possesses 100% spin polarization, which is important if it is to be used to generate a fully spin-polarized current for next-generation spintronic device applications (Wang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The general spin polarization ratio can be estimated as ¼ " À # = " þ # , in which " and # represent the spin-up states and spin-down states, respectively, extracted from the TDOS spectrum. AgCuF 3 possesses 100% spin polarization, which is important if it is to be used to generate a fully spin-polarized current for next-generation spintronic device applications (Wang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…6,7 Similarly, they also possess tunable electronic structure and high Curie temperatures. Similarly, MCoVZ (M = Lu, Y; Z = Si, Ge) studied by Wang et al 20 found the strain controls and changes the physical nature and electronic properties in them. Investigation of spin polarization and band structure in HA has been done in the past by many authors [16][17][18][19] and had found the ScFeCrT (T = Si, Ge), YRhTiGe, CoMnYZ (Z = Al, Ga, In), and FeRuCrP (FeRhCrP)-based HAs as half-metals.…”
Section: Introductionmentioning
confidence: 81%
“…To determine the stability of XA-type Sc 2 VGe compound, the cohesive energy (E c ) was calculated. The E c per unit cell can be expressed using the following formula [50]:…”
Section: Thermal Stability Of Xa-type Sc 2 Vgementioning
confidence: 99%
“…In addition, formation energy (E f ) is another way to describe the stability of crystals. We use the following formula to characterize E f per unit cell of Sc 2 VGe [50]:…”
Section: Thermal Stability Of Xa-type Sc 2 Vgementioning
confidence: 99%